Shopping for Health: Sodium - Wendy Dahl; Lauren Foster (EDIS)
FSHN10-06, a 4-page illustrated fact sheet by Wendy J. Dahl and Lauren Foster, provides information about sodium and offers tips on lowering sodium for a healthy diet. Includes references. Published by the UF Department of Food Science and Human Nutrition, July 2010.